The effect of training with accentuated eccentric load counter-movement jumps on strength and power characteristics of high-performance volleyball players - Sheppard, J.; Hobson, S.; Barker, M.; Taylor, K.; Chapman, D.; McGuigan, M.; Newton, R. (International Journal of Sports Science and Coaching, 2008)
The purpose of this study was to evaluate the training effects of using accentuated eccentric load counter-movement jumps on lower-body power characteristics in high-performance volleyball players. Sixteen volleyball players training full time with the state high-performance team participated in this 5 week training study. Prior to and at the completion of the study, jump squat testing with a lightweight (350 g) bar was conducted to determine kinetic and kinematic values for the lower body. Players were divided into either the accentuated eccentric load counter-movement jump group (AEJ) or normal (body-mass) counter-movement jump group (BMJ). The increases in displacement, velocity, and power values observed in the AEJ group were superior to those of the BMJ (p = 0.001-0.05, d = 1.06-1.97). The results of this study indicate that training with additional load during the eccentric phase of a counter-movement jump yields superior jump squat performance in comparison to typical counter-movement jump training in volleyball players who are already performing a high volume of jumping.